Pengaruh Game-Based Learning berbantuan Wordwall Terhadap Pemahaman Konsep Materi Pecahan pada Peserta Didik Kelas IV Sekolah Dasar Gugus R.A. Kartini - Huria Khansa Maulidian; Riyadi Riyadi; Sandra Bayu Kurniawan (Universitas Sebelas Maret, 2026)
This research focuses on the understanding of fraction concepts, which many fourth-grade elementary school students still struggle with due to the abstract nature of the subject and teacher-centered learning. The purpose of this study was to determine the effect of using a Game-Based Learning paradigm combined with Wordwall media on fourth-grade students' knowledge of fraction concepts. This research was conducted at Kartini Elementary School, Laweyan District, Surakarta City. This study used a quantitative approach, with a quasi experimental Unequal Control Group Design method. The samples were selected using cluster random sampling, consisting of an experimental group of 52 students who were taught using the Game-Based Learning model assisted by Wordwall and a control group of 50 students who received conventional instruction. Data were collected through a conceptual understanding test consisting of 20 multiple-choice questions. The data were analyzed using descriptive and inferential statistics, including the Kolmogorov–Smirnov normality test, Levene’s homogeneity test, balance test, and the Independent Samples t-test. The results showed that the experimental group achieved a higher mean posttest score (81.44) than the control group (70.70). The hypothesis testing also indicated a significance value of less than 0.05. The findings revealed that students conceptual understanding became clearly evident during the Wordwall gameplay stage, where students identified, matched, classified, and applied fraction concepts to solve game-based challenges. Therefore, the implementation of the Game-Based Learning model assisted by Wordwall had a significant effect and was more effective in improving fourth-grade elementary school students conceptual understanding of fractions than conventional learning.